2013
DOI: 10.1109/tbme.2012.2216879
|View full text |Cite
|
Sign up to set email alerts
|

Merging Person-Specific Bio-Markers for Predicting Oral Cancer Recurrence Through an Ontology

Abstract: Abstract-One of the major problems related to cancer treatment is its recurrence. Without knowing in advance how likely the cancer will relapse, clinical practice usually recommends adjuvant treatments that have strong side effects. A way to optimize treatments is to predict the recurrence probability by analyzing a set of bio-markers. The NeoMark European project has identified a set of preliminary bio-markers for the case of oral cancer by collecting a large series of data from genomic, imaging, and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In later studies, expression profiling studies to predict local recurrences have been tried as well, but the associations were generally not strong and profiles have not yet been adequately validated. [90,91] Nonetheless, the gains are high: postoperative radiotherapy or nowadays postoperative chemoradiation could be tailored on the basis of the presence of residual disease. An intrinsic problem remains that local recurrences may develop from two different sources: tumor cells and precancerous fields that stayed behind.…”
Section: Detection Of Minimal Residual Head and Neck Cancermentioning
confidence: 99%
“…In later studies, expression profiling studies to predict local recurrences have been tried as well, but the associations were generally not strong and profiles have not yet been adequately validated. [90,91] Nonetheless, the gains are high: postoperative radiotherapy or nowadays postoperative chemoradiation could be tailored on the basis of the presence of residual disease. An intrinsic problem remains that local recurrences may develop from two different sources: tumor cells and precancerous fields that stayed behind.…”
Section: Detection Of Minimal Residual Head and Neck Cancermentioning
confidence: 99%
“…An ontology is a broader knowledge model with a reasoning mechanism that facilitates knowledge on the semantic web [6]. Semantic web represents web content in a form that is easily machine process-able.…”
Section: Introductionmentioning
confidence: 99%
“…Semantic web knowledge will be organized in conceptual spaces according to meaning. Semantic web technologies are Ontologies, Explicit Metadata, Logic and Inference and Agents [6]. The term ontology originates from a philosophy which means nature of existence T.R Gruber's definition was redefined by R.Studer as "Ontology is an explicit and formal specification of a conceptualization" [3].…”
Section: Introductionmentioning
confidence: 99%
“…NeoMark is a FP7 EU-funded project that aims at improving the management of highly invasive and recurring cancers through a computer-assisted risk stratification and disease evolution prediction system. The system proposed in the project allows computing clinical, imaging and RNA data with smart algorithms and predicting the recurrence of Oral Squamous Cancer Carcinoma after surgery [167]. It comprises a central database for collecting patients data and review them with a web-based interface, an Image processing tool that is used to extract meaningful numeric features of tumours and suspicious lymph nodes from computed tomography (CT) and Magnetic Resonance Imaging (MRI) scans, a Genomic data filtering tool, which filters Feature Extraction data coming from micro-array analysis done on blood and tumour samples, a portable, real-time, low-cost quantitative real time polymerase chain reaction (qRT-PCR) tool that serves as a lab-on-a-chip alternative to micro-arrays for examining patient's RNA and a Data analysis module which is in charge of creating the patientspecific estimation model of cancer recurrence.…”
Section: Neomarkmentioning
confidence: 99%
“…The third scenario of this category is based on the NeoMark project [167] and on a study that identified genes signatures that predict response to different treatments in breast cancer [197].…”
Section: Relativementioning
confidence: 99%